Development of Spectrophotometric Method for Determination of Chlorpromazine-Hydrochloride in Pharmaceutical Preparations Via Use Ion-Exchange to Overcome the Interfering Ions - Bushra Basheer Kasim (Baghdad Science Journal, 2008)
In this scientific piece of research work, chlorpromazine CPZ (a psychaity drug) was determined spectrophotometrically using micro amount of reactant. In addition to micro amount of spectrophotometric reagent (400 ml). Various oxidizing agents were tested, including periodate, iodate, bromate, ferric nitrate, ferri cynate and persulphate. Oxidation reactions of the active ingradient (2,10-disubstituted phenothiazine) was used for the determination of CPZ in the presence of ferric nitrate. Detailed study of all chemical and physical parameters were studied. Ion-exchange columns were used to overcome the interfering ions. Percentage linearity was 99.86 for 0.04-8 mM CPZ, L.O.D. was 1´10-6M. Repeatabilety was better than 1.5%. The established results were followed to determine in some drugs.